Youth in farmer–herder conflicts: case studies from Sudan and Nigeria - Nassef, Magda; Sulieman, Hussein; Momale, Saleh; Higazi, Adam; Domingo, Pilar (SPARC Knowledge, 2025)
There is a significant gap in primary research on farmer–herder conflict in Africa. Specifically, youth – a demographic that constitutes the majority of the continent’s population – are notably under-represented in the literature. Through focus group discussions (FGDs) and key informant interviews (KIIs), SPARC has examined the experiences and roles of male and female youth in Sudan and Nigeria and how they are affected by farmer–herder conflict. In Sudan, the case study focuses on conflicts between farmers of mixed ethnic groups and Fallata pastoralists in Azaza Sogora village in Gadarif State. In Nigeria, the case study focuses on Tiv, Hausa and Fulani farming and pastoralist communities in Jangargari village in Awe Local Government, Nasarawa State. The fieldwork reveals that youth are key contributors to their communities and to local economies, and that they are highly affected by farmer–herder conflict. However, they are not very visible in research studies, which means the central role and potential of youth are insufficiently acknowledged, and their specific vulnerabilities are insufficiently addressed.